Lipid Bodies as Sites of Prostaglandin E2 Synthesis During Chagas Disease: Impact in the Parasite Escape Mechanism - Almeida, Patrícia E. de; Toledo, Daniel A. M.; Rodrigues, Gabriel S. C.; D’Avila, Heloisa (Frontiers in Microbiology, 2018)
During Chagas disease, the Trypanosoma cruzi can induce some changes in the host cells in order to escape or manipulate the host immune response. The modulation of the lipid metabolism in the host phagocytes or in the parasite itself is one feature that has been observed. The goal of this mini review is to discuss the mechanisms that regulate intracellular lipid body biogenesis in the course of this parasite infection and their meaning to the pathophysiology of the disease. The interaction host-parasite induces lipid body (or lipid droplet) formation in a Toll-like receptor 2–dependent mechanism in macrophages and is enhanced by apoptotic cell uptake. Simultaneously, there is a lipid accumulation in the parasite due to the incorporation of host fatty acids. The increase in the lipid body accumulation during infection is correlated with an increase in the synthesis of PGE2 within the host cells and the parasite lipid bodies. Moreover, the treatment with fatty acid synthase inhibitor C75 or nonsteroidal anti-inflammatory drugs such as NS-398 and aspirin inhibited the lipid body biogenesis and also induced the down modulation of the eicosanoid production and the parasite replication. These findings show that lipid bodies are organelles up modulated during the course of infection. Furthermore, the biogenesis of the lipid body is involved in the lipid mediator generation by both the macrophages and the parasite triggering escape mechanisms.